Molecular mechanism of GANT61 combined with doxorubicin in the treatment of gliomas based on network pharmacology - Jing Chen (Elsevier, 2022)
Background: Gliomas are common malignant intracranial tumors. Efficacious targeted therapy against gliomas is lacking. Results: GANT61 combined with the chemotherapy drug doxorubicin for treatment of glioma (LN-229) cells, and the effect of their combination, was tested. The molecular mechanism was explored by target prediction, along with functional analysis using the Gene Ontology (GO) database, enrichment analysis using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, construction of protein–protein interaction (PPI) networks, and protein expression. Combination of GANT61 plus doxorubicin could inhibit the growth of LN-229 cells effectively. Wound-healing data and expression of migration proteins related to epithelial-to-mesenchymal transition showed that this combination could inhibit the migration of LN-229 cells. Sixty-one targets of drug and disease intersected. Functional analysis revealed negative regulation of apoptosis, positive regulation of cell proliferation, and other biological processes related to apoptosis and proliferation. Pathway-enrichment analysis showed drug combination to be related to the cyclic adenosine monophosphate signaling pathway, pathways in cancer, and Hedgehog signaling pathway. Measurement of expression of several proteins related to these pathways revealed expression of BIRC5, GLi1 and GLi2, MMP3 and MMP9 proteins to decrease, and expression of MDM2 and P53 proteins to decrease and increase, respectively. Conclusions: This study provides a: (a) new direction for targeted therapy of gliomas; (b) theoretical basis for drug research and molecular-mechanism research on gliomas.How to cite: Chen J, Zhang Q, Zhang G et al. Molecular mechanism of GANT61 combined with doxorubicin in the treatment of gliomas based on network pharmacology. Electron J Biotechnol 2021;55. https://doi.org/10.1016/j.ejbt.2021.11.001.